2016
DOI: 10.1016/j.amsu.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 1869 thyroid ultrasound-guided fine-needle aspiration biopsies between general surgeons and interventional radiologists

Abstract: BackgroundThyroid nodules are commonly encountered problems in clinical practice. For patients who have a thyroid nodule, the fine-needle aspiration biopsy (FNAB) is the most important test, as it is the most reliable diagnostic method for distinguishing between benign thyroid nodules and cancerous nodules. FNAB is able to be performed either via an ultrasound (USG) or alone and is the first choice when it comes to diagnosing thyroid nodules, given that it is cheap, safe and provides accurate results.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…28 Hilmi Bozkurt et al reported that US-guided FNAC can be performed with a low non-diagnostic rate as experience grows. 31 The following limitations were inherent in this study and may have biased the results. The first audit cycle demonstrated a very high rate of insufficiency in thyroid FNAC (higher than that reported in the literature) (see Figure 2).…”
Section: Fnac = Fine-needle Aspiration Cytologymentioning
confidence: 98%
“…28 Hilmi Bozkurt et al reported that US-guided FNAC can be performed with a low non-diagnostic rate as experience grows. 31 The following limitations were inherent in this study and may have biased the results. The first audit cycle demonstrated a very high rate of insufficiency in thyroid FNAC (higher than that reported in the literature) (see Figure 2).…”
Section: Fnac = Fine-needle Aspiration Cytologymentioning
confidence: 98%
“…Today, FNAB represents the gold standard for the diagnosis of the nature of thyroid nodules due to its safety, reliability, low costs and high tolerability by the patients (3,20). According to the newly reviewed guidelines for thyroid nodules (<5 mm), US monitoring is always recommended.…”
Section: Thyroid Fine-needle Aspiration Biopsy (Fnab)mentioning
confidence: 99%
“…Exclusion criteria include presence of hot nodules on scintigraphy and/or patients with severe coagulation disorders. US guidance makes FNAB safer and is now considered mandatory, allowing real-time control of the tip of the needle when approaching the target areas avoiding the vascular structures (1,3,(21)(22)(23). Five cytologic diagnostic categories are considered for the diagnosis of thyroid nodules (1): nondiagnostic, benign, indeterminate, suspicious for malignancy, and malignant.…”
Section: Thyroid Fine-needle Aspiration Biopsy (Fnab)mentioning
confidence: 99%
See 2 more Smart Citations